MODEL KEPEMIMPINAN KIAI DI PESANTREN MODERN - Adisel, Adisel; Muhamad Suparji; Mufid Faruq Aziz; Niftah Handayani; Winda Sari (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
This study aims to determine the implementation of the management and leadership of the kiai at the Darunnajah Islamic Boarding School in Jakarta so that it continues to exist and even becomes a prototype of the leadership and management of modern Islamic boarding schools in Indonesia. The research used a descriptive qualitative method which was carried out by collecting data obtained from documentation, observation and interviews, and supported by literature studies, both from books and journals. The results of the study show that the modernity of Pondok Darunnajah is seen in the management implementation which is different from other Islamic boarding schools in general. Darunnajah Islamic Boarding School management is carried out based on the principles of transparency and accountability as well as togetherness. Darunnajah Islamic Boarding School adheres to a collective leadership model